Enhancement of the immune response to hepatitis B virus vaccine by antigen specific IgM - (:unkn) unknown (ELSEVIER SCIENCE BV, 2000)
In the present study, modulation of antibody response induced by Hepatitis B virus vaccine-IgM complex was investigated. Purified IgM-type anti HBv monoclonal antibody (1B11) was complexed to commercially available HBv vaccine (GenHevac B Pasteur, France) at varying concentrations of HBsAg (0.5, 1, 1.5 mu g of HBsAg) and used to immunize BALB/c mice. An enhanced humoral immune response was obtained with the HBv vaccine IgM complex at all the doses compared with those immunized by vaccine alone and increased antibody levels were observed with increased concentrations of HBsAg in vaccine formulation. Immunization with HBv vaccine IgM complex mostly generated IgG-type antibodies in the sera of mice, and also gave rise to the development of hybrid cells which predominantly produced IgG-type monoclonal antibodies. Hence, results from this study indicate that 1B11 call be effectively used to obtain a better immune response to HBv vaccine. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: hepatitis B virus vaccine; aluminum adjuvant; antibody response; IgM-type anti HBv monoclonal antibody; hybridoma; ANTIBODY COMPLEXES; MEMORY CELLS; MEDIATED ENHANCEMENT; SURFACE-ANTIGEN; MICE; ADJUVANTS; GENERATION; IMMUNOGENICITY; ACTIVATION; ALUM